2006
DOI: 10.1111/j.1468-1331.2006.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guideline on diagnosis and management of post‐polio syndrome. Report of an EFNS task force

Abstract: Post‐polio syndrome (PPS) is characterized by new or increased muscular weakness, atrophy, muscle pain and fatigue several years after acute polio. The aim of the article is to prepare diagnostic criteria for PPS, and to evaluate the existing evidence for therapeutic interventions. The Medline, EMBASE and ISI databases were searched. Consensus in the group was reached after discussion by e‐mail. We recommend Halstead's definition of PPS from 1991 as diagnostic criteria. Supervised, aerobic muscular training, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(131 citation statements)
references
References 74 publications
2
113
0
13
Order By: Relevance
“…A study conducted in Brazil reported that CI, among other symptoms, is more prevalent among women (75%) 8 . In this study, our patients were predominantly female, which is consistent with other PPS studies conducted in Brazil 4,5 as well as internationally [17][18][19] . In Brazil, the predominance of female patients is attributed to the fact that women seek health services more often than men (excluding one case in which gender predominance was reversed) 20 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A study conducted in Brazil reported that CI, among other symptoms, is more prevalent among women (75%) 8 . In this study, our patients were predominantly female, which is consistent with other PPS studies conducted in Brazil 4,5 as well as internationally [17][18][19] . In Brazil, the predominance of female patients is attributed to the fact that women seek health services more often than men (excluding one case in which gender predominance was reversed) 20 .…”
Section: Discussionsupporting
confidence: 79%
“…In Brazil, the predominance of female patients is attributed to the fact that women seek health services more often than men (excluding one case in which gender predominance was reversed) 20 . The average age of patients in this study was 48.3 years, that is similar to Brazilian and international studies in which an average age of 50 to 63 years was reported 17,21,22 . The level of patient schooling averaged 13.20±1.57 years.…”
Section: Discussionsupporting
confidence: 72%
“…The mild pain at the end of the day that patients reported could be related to postpolio muscle pain in the paralytic group and remnant leg length discrepancy in the contralateral group, but this is speculative. We recommend abductor strengthening exercises in the paralytic group [4,12,38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact incidence has not been established, symptoms occur decades after recovery from acute polio. [1][2][3] Pyridostigmine, an anticholinesterase agent, inhibits the hydrolysis of acetylcholine, prolonging its effects in the neuromuscular junction. Studies suggest that neuromuscular junction transmission in postpoliomyelitis syndrome may improve with anticholinesterases.…”
Section: Rationalementioning
confidence: 99%